Qualidade de vida de idosas com incontinência urinária - Santos, Kamyla Félix Oliveira dos (2013)
Introduction: In the context of aging, diseases for which age itself is a risk factor, such as urinary incontinence, tend to assume epidemic dimensions. Urinary incontinence is a clinical condition which may compromise different dimensions of the person and, thus, evaluating its impacts on the quality of life of elderly women, most frequently affected by the problem, becomes relevant. Objective: Evaluate the quality of life of elderly women with urinary incontinence. Materials and methods: This is a study with an epidemiological nature, descriptive, exploratory, cross-sectional, conducted along with the population of elderly women, aged 60 years or older, assisted at the Center for Integral Health Care for the Elderly Person in Joao Pessoa, Paraiba, Brazil. The sample consisted of 194 elderly women, assisted at the service concerned in the specialties of geriatrics and gynecology, who reported urinary incontinence by themselves. Data collection was conducted within the period from June to August 2012, using the structured interview technique with socio demographic and clinical variables, besides the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) and the King's Health Questionnaire (KHQ), used for measuring the impact of urinary incontinence on the quality of life of the surveyed women. After collecting the information, they were typed and organized into a computerized database through the software Statistical Package for the Social Sciences, version 20.0, to facilitate its statistical approach. Results: One found out a higher percentage of young elderly women, with a mean age of 70.62 years; widows (39.7%); low education (52.6%); and an income up to 2 minimum wages (79.4%). Regarding the clinical features, the most frequently observed morbidities were: arterial hypertension (87.2%) and osteoporosis (34.8%), being frequent the comorbidities and the use of medicines (92.3%), standing out the antihypertensive agents (63.7%). A minority of the women had the habit of smoking (7.2%) and most of them (82%) didn t seek assistance for the management of urinary incontinence. The most common type was the urge urinary incontinence. Taking into account the impact of urinary incontinence on the quality of life of the elderly women, measured through the ICIQ-SF, one obtained a mean score of 10.22, classified as very severe impact. One identified that the stress urinary incontinence and mixed urinary incontinence showed a statistically significant relation (p < 0.001). Based on the results obtained through KHQ, one also found out that the urinary incontinence exerted a negative influence on the quality of life of respondents in the domains of general health, incontinence impact, severity measures, and emotions. Conclusion: One concludes that urinary incontinence, especially the urge, had a negative impact on the quality of life of the elderly women. The results reinforce the need for health professionals adequately addressing this problem and, also, for health services concerning themselves in organizing multidisciplinary teams trained to care for women with urinary incontinence, in order to guide them and offer conditions for an embracing and individualized care.